The Role of Students in Realizing Excellent and Moral Graduates at Alhuda Islamic Junior High School - Dian Novitasari; Luciana Wardani; Luthfiyah Awwalul Karimah (Green Publisher Indonesia, 2021)
This writing aims to find out about the role of students in creating superior and moral graduates. This research was conducted at Alhuda Islamic Junior High School in Lamongan Regency with uses a qualitative method. The technique of collecting data on this writing is done by means of interviews and observations. The result of the research is by screening students to be able to create superior and moral graduates. The role of students is by screening students who will register at the school. Of course, prioritizing the ability of students who later can provide guidance or coaching to be able to produce quality graduates. Then in realizing excellent and moral graduates, the role of students at Alhuda Islamic Junior High School is by increasing the development of Intra School Organization (OSIS). The goal is none other than introducing students to organize, direct and control student activities. As well as fostering and implementing coordination of security, health, cleanliness, order, shade, beauty and kinship.